The Role of Law in Addressing Racial Disparities in the Criminal Justice System: A Social Science Perspective - Rino Noviyantho (Journal of Public Representative and Society Provision, 2021)
From a sociological viewpoint, this article explores how the legislation might help reduce racial inequalities within the criminal justice system. Empirical evidence on racial bias and inequities in policing and the criminal justice system is analyzed, with help from theoretical frameworks like critical race theory and procedural justice theory. We also examine the opposing interests and ambitions of the many political actors participating in the reform of the police force. Using descriptive data, we can better understand the problems currently plaguing law enforcement and better articulate the critical need for change. In order to construct a more just and equitable criminal justice system, we end by stressing the significance of taking a data-driven and nuanced approach to resolving these concerns. Law, racial inequality, the criminal justice system, and police reform are all topics covered in this article.